Gentrification, Market Regimes, and the New Entrepreneurial Principal: Enacting Integration or Displacement?. Issue 2 (3rd April 2019) - McGhee, Chy; Anderson, Gary
ABSTRACT: The last 30 years of school reform have left us with an increase in urban school districts with market regimes (school choice, charter schools, and managerialism). Sociologists of the professions have documented the extent to which these reforms tend to be reshaping public sector professionals, replacing an ethos of public service with one of competition and entrepreneurialism. Meanwhile, as cities become more gentrified, some argue that there are both opportunities for greater class and racial integration and the danger of increased segregation and displacement for low-income families of color. Principals are key gatekeepers who are expected to mediate between the expectations of various groups of parents, community members, and teachers. Yet, like other public-sector professionals, they are increasingly controlled from a distance through the discipline of the market, outcomes metrics, and other managerialist policies. In this article, we will explore the intersection of these three developments (market regimes, the "new professional, " and gentrification) through a review of current literature and discuss implications for principals who want to be advocates for their low-income communities of color while also desegregating their schools. We will also suggest some research questions to explore the role of school administrators within the confluence of new market regimes and gentrification in an increasing number of urban centers.